Optimal Renewable Energy Distribution Between Gasifier and Electrolyzer for Syngas Generation in a Power and Biomass-to-Liquid Fuel Process - Putta, Koteswara R.; Pandey, Umesh; Gavrilovic, Ljubisa; Rout, Kumar R.; Rytter, Erling; Blekkan, Edd A.; Hillestad, Magne (Frontiers in Energy Research, 2022)
By adding energy as hydrogen to the biomass-to-liquid (BtL) process, several published studies have shown that carbon efficiency can be increased substantially. Hydrogen can be produced from renewable electrical energy through the electrolysis of water or steam. Adding high-temperature thermal energy to the gasifier will also increase the overall carbon efficiency. Here, an economic criterion is applied to find the optimal distribution of adding electrical energy directly to the gasifier as opposed to the electrolysis unit. Three different technologies for electrolysis are applied: solid oxide steam electrolysis (SOEC), alkaline water electrolysis (AEL), and proton exchange membrane (PEM). It is shown that the addition of part of the renewable energy to the gasifier using electric heaters is always beneficial and that the electrolysis unit operating costs are a significant portion of the costs. With renewable electricity supplied at a cost of 50 USD/MWh and a capital cost of 1,500 USD/kW installed SOEC, the operating costs of electric heaters and SOEC account for more than 70% of the total costs. The energy efficiency of the electrolyzer is found to be more important than the capital cost. The optimal amount of energy added to the gasifier is about 37–39% of the energy in the biomass feed. A BtL process using renewable hydrogen imports at 2.5 USD/kg H2 or SOEC for hydrogen production at reduced electricity prices gives the best values for the economic objective.